La geomatica per i sette decimi del globo - Santarsiero, Domenico (GEOmedia, 2009)
Geomatics for the 7/10 of the globe The article underlines the multidisciplinary aspects of water studies. The water context is a complex reality, especially if the entire cycle of skills and knowledge required is considered. The complexity increases as one moves from the river to the sea and ocean level. The focus of the article remains on geomatic technologies and on the fields of hydrography, oceanography and water management.